2022 IEEE Radar Conference (RadarConf22) 2022
DOI: 10.1109/radarconf2248738.2022.9764354
|View full text |Cite
|
Sign up to set email alerts
|

Toward Data-Driven STAP Radar

Abstract: Catalyzed by the recent emergence of site-specific, high-fidelity radio frequency (RF) modeling and simulation tools purposed for radar, data-driven formulations of classical methods in radar have rapidly grown in popularity over the past decade. Despite this surge, limited focus has been directed toward the theoretical foundations of these classical methods. In this regard, as part of our ongoing datadriven approach to radar space-time adaptive processing (STAP), we analyze the asymptotic performance guarante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Our objective is to predict targets locations from these 3D heatmap tensors using a robust deep learning framework for target localization. In our prior work (see [1]), we demonstrated that this framework achieves considerable gains over traditional approaches that invoke linear estimation principles. However, much of this analysis was performed in a 'matched' setting, where our convolutional neural network (CNN) architecture was trained and validated on heatmap tensors from the same constrained area (the 'original platform location' instance in [2]).…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Our objective is to predict targets locations from these 3D heatmap tensors using a robust deep learning framework for target localization. In our prior work (see [1]), we demonstrated that this framework achieves considerable gains over traditional approaches that invoke linear estimation principles. However, much of this analysis was performed in a 'matched' setting, where our convolutional neural network (CNN) architecture was trained and validated on heatmap tensors from the same constrained area (the 'original platform location' instance in [2]).…”
Section: Introductionmentioning
confidence: 88%
“…In our prior work (see [1]), we demonstrated that this framework achieves considerable gains over traditional approaches that invoke linear estimation principles. However, much of this analysis was performed in a 'matched' setting, where our convolutional neural network (CNN) architecture was trained and validated on heatmap tensors from the same constrained area (the 'original platform location' instance in [2]). To benchmark the localization performance of our CNN framework across 'mismatched' scenarios -where network training and testing is performed with tensors from disparate constrained areas -we separately used the mean normalized output SCNR metric [8].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations